English Language Teachers’ Professional Development Needs in Ethiopia - M.K. Abrar (Психолого-педагогические исследования)
The purpose of this study was to investigate the ongoing professional development needs of English language teachers in primary school. A mixed methods design was employed in the study. The participants were sixty-four primary school English language teachers. They were selected randomly from six elementary schools. A survey and an interview were used to collect data. All the teachers took part in the survey. Additionally, eight of them were observed while teaching in the classroom. Furthermore, six trainers participated in key informant interviews and focus group discussions. The results of the survey show that the majority of teachers estimate their speaking and reading skills at an intermediate level, and there is a moderate significant correlation between teachers’ evaluations of speaking and reading skills. Based on the interview results, qualitative data were collected and analyzed to corroborate the survey findings. The themes were categorized and interpreted. It was revealed that the teachers have severe needs for English language proficiency and must continuously develop their pedagogical and subject-matter knowledge. On the basis of the findings, suggestions were made to the ministry of education to prepare professional development activities based on the teachers’ needs.